Subject-specific factors affecting particle residence time distribution of left atrial appendage in atrial fibrillation: A computational model-based study - Sanatkhani, Soroosh; Nedios, Sotirios; Menon, Prahlad G.; Saba, Samir F.; Jain, Sandeep K.; Federspiel, William J.; Shroff, Sanjeev G. (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) is a prevalent arrhythmia, that causes thrombus formation, ordinarily in the left atrial appendage (LAA). The conventional metric of stroke risk stratification, CHA2DS2-VASc score, does not account for LAA morphology or hemodynamics. We showed in our previous study that residence time distribution (RTD) of blood-borne particles in the LAA and its associated calculated variables (i.e., mean residence time, tm, and asymptotic concentration, C∞) have the potential to improve CHA2DS2-VASc score. The purpose of this research was to investigate the effects of the following potential confounding factors on LAA tm and C∞: (1) pulmonary vein flow waveform pulsatility, (2) non-Newtonian blood rheology and hematocrit level, and (3) length of the simulation. Methods Subject-Specific data including left atrial (LA) and LAA cardiac computed tomography, cardiac output (CO), heart rate, and hematocrit level were gathered from 25 AF subjects. We calculated LAA tm and C∞ based on series of computational fluid dynamics (CFD) analyses. Results Both LAA tm and C∞ are significantly affected by the CO, but not by temporal pattern of the inlet flow. Both LAA tm and C∞ increase with increasing hematocrit level and both calculated indices are higher for non-Newtonian blood rheology for a given hematocrit level. Further, at least 20,000 s of CFD simulation is needed to calculate LAA tm and C∞ values reliably. Conclusions Subject-specific LA and LAA geometries, CO, and hematocrit level are essential to quantify the subject-specific proclivity of blood cell tarrying inside LAA in terms of the RTD function.